Circulating miR-30b and miR-30c predict erlotinib response in EGFR-mutated non-small cell lung cancer patients. (September 2019) - Hojbjerg, Johanne Andersen; Ebert, Eva Boysen Fynboe; Clement, Michelle Simone; Winther-Larsen, Anne; Meldgaard, Peter; Sorensen, Boe
Highlights: Intrinsic resistance to EGFR TKI is an important clinical problem. This was a prospective observational study. Patients had NSCLC, adenocarcinoma and an activating mutation in the EGFR . Plasma levels of miRNA 30b and 30c predicted erlotinib-treatment outcome. Abstract: Objectives: MiR-30b, miR-30c, miR-221 and miR-222 are known to induce gefitinib resistance in lung cancer cell lines with activation of mutations in the epidermal growth factor receptor ( EGFR ). However, the role of these four microRNAs in tyrosine kinase inhibitor (TKI)-resistance in non-small cell lung cancer (NSCLC) patients is unknown. Thus, the aim of this study was to investigate the predictive value of miR-30b, miR-30c, miR-221 and miR-222 in plasma from EGFR -mutated lung cancer patients receiving erlotinib. Materials and methods: The cohort consisted of 29 EGFR -mutated lung cancer patients receiving erlotinib. Plasma levels of miR-30b, miR-30c, miR-221 and miR-222 were analyzed by qPCR from blood samples collected before treatment start. Plasma concentration of each microRNA was correlated to clinical outcome. Results: Plasma concentrations of miR-30b and miR-30c could be determined in all 29 patients. Low plasma concentrations of miR-30b and miR-30c showed significant correlation with superior progression-free survival (PFS) (miR-30b: HR = 0.303 [0.123–0.747], p < 0.05; miR-30c: HR = 0.264 [0.103–0.674], p < 0.05). Low plasma concentrations of miR-30c were also significantly correlated with superior overall survival (OS) (HR = 0.30 [0.094–0.954], p < 0.041). Conclusion: High plasma concentrations of miR-30b and miR-30c predicted shorter PFS and OS. This implies that miR-30b and miR-30c could have clinical potential as biomarkers in EGFR -mutated lung cancer patients.